Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

eIF6 affects the occurrence and development of esophageal cancer - Cong-Gai Huang; Xin Zhou; Ran Huang; Hui-Ling Zhang; Chen-Xi Li; Fei Du; Hong Lei; Qiong Dai; Zhi-Hui Yang (Molecular Biology Reports, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Climate value of energy storage for floating photovoltaic across China’s decarbonizing power grids - Ran Hao; Xin Sun; Yuchen Zhao; Chengchao Huang; Lili Yang; Weiqiao Wang; Junyu Sun; Li Fei; Lihao Zhao (ENGINEERING Environment, 2026)

Insights into EPS-mediated simultaneous dewatering and stabilization of landfilled tannery sludge via combined chemical conditioning and PVD-vacuum preloading - Yang Xu; Fei Jin; Xiaowen Liu; Weixin Cheng; Ran Yu; Jia-Lei Wan; Jia-Hao Xie; Yan-Jun Du (Chemical Engineering Journal, 2026)

Multi-frequency seismic evidence for phase transitions in a rock–ice avalanche-triggered cascading Hazard in the Yanzigou Basin, Southeastern Tibetan Plateau - Zhaoying Wu; Zongji Yang; Qiao Liu; Fei Ran; Bo Zhang; Zhiyong Huang; Pan Chen; Bo Pang (Engineering Geology, 2026)

Direct synthesis of non-migratory, intrinsically antioxidant ultra-high molecular weight polyethylene by nickel catalysis - Fei-Ran Yang; Wen-Bing Wang; Tian-Ming Yang; Hao-Xiang Sun; Quan Wang; Meng-He Xu; Jia-Wei Chen; Chen Zou (Chemical Engineering Journal, 2026)

Associations between non-methane volatile organic compounds and cause-specific mortality across 14 major categories - Shengtao Wei; Ge Chen; Lan Chen; Zijun Yang; Fei Tian; Peng Hu; Kin Fai Ho; Shanshan Ran; Dashan Zheng; Hualiang Lin (Environmental Pollution, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Redox homeostasis regulation during the formation of archeospores in Neopyropia yezoensis - Li-Fei Yang; An-Ran Shen; Da-Hai Gao (Algal Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

An optimal method for GNSS water vapor tomography based on parameter adaptation - Fei Yang; Ruixian Hao; Haoyu Wang; Lei Wang; Zhicai Li; Junxi Zheng; Yingying Wang; Ran Chen (GPS Solutions, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Associations of air pollution and genetic risk and their interaction with risk of Alzheimer’s disease: identification of risk loci and potential biological pathways - Shanshan Ran; Jingyi Zhang; Miao Cai; Lan Chen; Zhengmin Qian; Fei Tian; Gan Wu; Ri’enna Boyd; Stephen Edward McMillin; Huai-cai Zeng; Yin Yang; Hualiang Lin (GeroScience, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Dual-interface MXene engineering for low-noise perovskite photodetectors in optical communication and health monitoring - Shareen Shafique; Haodong Wang; Yegang Lu; Taimoor Iqbal; Yuheng Wang; Baihui Shen; Ran Zhao; Li Sheng; Cheng Yang; Muhammad Sulaman; Fei Zheng; Ziyang Hu (Chemical Engineering Journal, 2026)

The detection method of ammonia nitrogen concentration in water bodies based on hyperspectrum - Yahe Di; Tao Li; Hui Ran; Rui Yang; Fei He; Aixuan Li; Chenzhan Tang; Wenjing Tian (Journal of Water Process Engineering, 2025)

Late Permian strike-slip tectonics in the northern North China Craton: new insights from geological and geophysical data of the Longwangmiao granitic pluton - Chao Song; Wei Lin; Wei Wei; Lingtong Meng; Yang Chu; Qinying Wu; Zhao Guo; Yin Wang; Ran An; Fei Liu; Jinhui Yang (Journal of Asian Earth Sciences, 2025)

Pregnant PM2.5 exposure promotes uterine contractility via miR-200a-PGR-oxytocin signaling pathway leading to preterm birth - Jingyi Zhang; Shanshan Ran; Shengtao Wei; Zijun Yang; Huaicai Zeng; Guang Jia; Zhangjian Chen; Lan Chen; Fei Tian; Ge Chen; Zilong Zhang; Hualiang Lin (Atmospheric Environment, 2025)

Chemotaxis-driven Stenotrophomonas pavanii surface-aggregated FastPETase system for in situ degradation of PET microplastics - Si-Qi Chen; Qing-Song Huang; Yang Li; Hao-Ran Zhang; Yan Huang; Jing Wu; Sheng Chen; Zheng-Fei Yan (Chemical Engineering Journal, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

In vitro and in vivo evidence on the association of pregnant PM2.5 exposure with preterm birth and potential role of placental miRNA-21 regulating TLR4/NF-κB and activating NLRP3 inflammasome - Shanshan Ran; Wenxue Li; Zijun Yang; Jingyi Zhang; Zhangjian Chen; Guang Jia; Qingmei Lin; Huai-cai Zeng; Yin Yang; Zilong Zhang; Yonggui Gao; Lan Chen; et al. (Journal of Hazardous Materials, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Assessment of carbon sinks caused by the chemical weathering of carbonate rocks under the influence of exogenous acids: Methods, progress, and prospects - Luhua Wu; Xiaoyong Bai; Chaojun Li; Huiwen Li; Yue Cao; Chen Ran; Sirui Zhang; Lian Xiong; Chaochao Du; Guangjie Luo; Fei Chen; Heng Wei; et al. (Science China Earth Sciences, 2025)

Vertical distributions of dimethyl sulfide and dimethylsulfoniopropionate and impacts of DMSP lyase and bacteria in the Yellow Sea and East China Sea - Xin-Ran Song; Qian-Yao Ma; Juan Yu; Gui-Peng Yang; Rong Chen; Zheng-Yu Zhang; Yu Jiang; Long-Fei Liu (Marine Environmental Research, 2025)

Chronic intermittent hypoxia modulates energy metabolic pathways and improves hypoxia tolerance capacity in golden pompano, Trachinotus blochii - Geng Hui Fang; Xiao Li Zhou; Chun Li Ran; Chun Xiu Jin; Shao Yang Bu; Yue Chen; Yong Gong; Zeng Tan Hu; Fei Biao Song; Jian Luo; Jun Long Sun (Science of The Total Environment, 2025)

Tillage effects on maize yield, N use efficiency and GHG emissions under parallel N application in Northwest China - Hao-yang Wu; Lin-ling Ran; Jun-qiang Wang; Shuang Yan; Yun-yin Xue; Fei Xia; Hao Shi; Wei Wei; Yu Zhang; Shai-kun Zheng (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

An artificial mud brick structural coating endows bamboo with excellent flame retardant, smoke suppression and reliable fire warning performance - Fei Yang; Ying Ran; Qichao Bao; Pengxu Tao; Jianliang Ding; Shengnan Zhang; Jiawei Zhu; Chungui Du (Journal of Cleaner Production, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

A novel dual-emission fluorescence sensor with different responsive modes for non-invasive and simultaneous quantitative detection of carbaryl and imidacloprid - Yi-Fan Xia; Hou-Qun Yuan; Zhi-Qiang Cai; Le Fang; Zhen-Chong Dou; Qian-Wen Yang; Yi-Xuan Hu; Ran Wang; Yu-Fei Zhong; Guang-Ming Bao (Chemical Engineering Journal, 2025)

An active-conductive layer stacked sensor platform for real-time detection of heavy metal ions - Yuping Yang; Lijia Xu; Yongpeng Zhao; Yuchao Wang; Zhijun Wu; Zhiliang Kang; Zhiyong Zou; Hui Huang; Yong He; Fei Liu; Zuoliang Tang; Ao Feng; et al. (Chemical Engineering Journal, 2025)

Microplastics and copper impacts on feeding, oxidative stress, antioxidant enzyme activity, and dimethylated sulfur compounds production in Manila clam Ruditapes philippinarum - Yu Jiang; Juan Yu; Ji-Yuan Tian; Gui-Peng Yang; Long-Fei Liu; Xin-Ran Song; Rong Chen (Marine Pollution Bulletin, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Size-dependent influences of nano- and micro-plastics exposure on feeding, antioxidant systems, and organic sulfur compounds in ciliate Uronema marinum - Long-Fei Liu; Juan Yu; Yu Jiang; Qian Liu; Yong Jiang; Rong Chen; Gui-Peng Yang; Xin-Ran Song (Environmental Pollution, 2024)

Impacts of nano- and micro-plastics exposure on zooplankton grazing, bacterial communities, and dimethylated sulfur compounds production in the microcosms - Yu Jiang; Juan Yu; Rong Chen; Su Wang; Gui-Peng Yang; Long-Fei Liu; Xin-Ran Song (Environmental Pollution, 2024)

Effects of light spectra on growth and compositions of biomass, fatty acids, and pigments in three typical microalgae from different phyla - Fei Kong; Jiaxing Zhang; Dongzi Yang; Yao Zhou; Yanrong Li; Deshui Chen; Xiaojun Yan; Zhaoshou Ran; Jilin Xu (Journal of Oceanology and Limnology, 2024)

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Visual environment in schools and student depressive symptoms: Insights from a prospective study across multiple cities in eastern China - Xiyan Zhang; Jiawen Tang; Yan Wang; Wenyi Yang; Xin Wang; Ran Zhang; Jie Yang; Wei Lu; Fei Wang (Environmental Research, 2024)

Patterns and drivers of organic carbon in hydromorphic soils across inland aquatic-terrestrial ecotones at the global scale - Yiguo Ran; Peng Wang; Fei Ye; Junfeng Qu; Yang Ning; Yanshuo Zhang; Zhaofei Wen; Shengjun Wu; Ping Huang (CATENA, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Skillful prediction of boreal winter-spring seasonal precipitation in Southern China based on machine learning approach and dynamical ENSO prediction - Ting-wei Cao; Yi-ran Xu; Fei Zheng; Ruo-wen Yang (Theoretical and Applied Climatology, 2024)

A novel fluorescence platform for specific detection of tetracycline antibiotics based on [MQDA-Eu3+] system - Jia-Mei Ran; Liu Yang; Chun-Tong Liu; Qiu-Huan Liu; Yu-Long Liu; Shi-Jie Li; Ying Fu; Fei Ye (Science of The Total Environment, 2024)

Effects of micro- and nano-plastics on growth, antioxidant system, DMS, and DMSP production in Emiliania huxleyi - Juan Yu; Ji-Yuan Tian; Yu Jiang; Xue-Dan Wang; Xin-Ran Song; Long-Fei Liu; Gui-Peng Yang (Environmental Pollution, 2024)

Influence of the community assemblage on sulfur distributions in the South China sea - Hao-Quan Zhang; Juan Yu; Jing-Guang Lai; Gui-Peng Yang; Long-Fei Liu; Yu Jiang; Xin-Ran Song; Yong-Qiao Chen; Hou-Jin Zhou; Qi Zhang (Marine Environmental Research, 2024)

Ecoregion-wise fractional mapping of tree functional composition in temperate mixed forests with sentinel data: Integrating time-series spectral and radar data - Ziyu Lin; K.H. Cheng; Dedi Yang; Fei Xu; Guangqin Song; Ran Meng; Jing Wang; Xiaolin Zhu; Michael Ng; Jin Wu (Remote Sensing of Environment, 2024)

Spatiotemporal distribution and impact factors of GNSS-PWV in China based on climate region - Fei Yang; Xu Gong; Zhicai Li; Yingying Wang; Shiji Song; Haoyu Wang; Ran Chen (Advances in Space Research, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Micro- and nano-hybrid cellulose fibers prepared by straightforward and high-efficiency hot water soaking-assisted colloid grinding for high-performance cellulose paper - Huiping Lin; Guolong Hong; Mingen Fei; Yiqin Shen; Xinxiang Zhang; Jian Li; Wenbin Yang; Ran Li (Carbohydrate Polymers, 2024)

Storage, form, and influencing factors of karst inorganic carbon in a carbonate area in China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; et al. (Science China Earth Sciences, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Identifying cadmium and lead co-accumulation from living rice blade spectrum - Shuangyin Zhang; Teng Fei; Yiyun Chen; Jiaxin Yang; Ran Qu; Jian Xu; Xiao Xiao; Xuejun Cheng; Zhongzheng Hu; Xuedong Zheng; Dengzhong Zhao (Environmental Pollution, 2023)

Intelligent bamboo: A splendid flame retardant, fire warning and photothermal sterilization nanocoating via low-temperature evaporation induced self-assembly - Fei Yang; Qichao Bao; Chungui Du; Jiawei Zhu; Yuting Wang; Yuran Shao; Ying Ran (Chemical Engineering Journal, 2023)

Recent progress in γ-Fe2O3-based catalysts: An overview of the synthesis and applications in environmental remediation - Yuzhuo Zhou; Xin Yang; Chen Gong; Fei Zhu; Jian Wang; Yongfeng Qi; Kai Huang; Jiang Wu; Ran Chen; Yi Liu (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Accumulation characteristics and structural properties of starch in different spatial positions of wheat endosperm under nitrogen application - Jiaqing Yang; Peiyao Liu; Liping Ran; Gang Chen; Xurun Yu; Fei Xiong (Journal of Cereal Science, 2023)

Corrigendum to “Long-term environmental levels of microcystin-LR exposure induces colorectal chronic inflammation, fibrosis and barrier disruption via CSF1R/Rap1b signaling pathway” [J Hazard Mater 440 (2022) 129793] - Yue Yang; Hui Wang; Xiaoyan Wang; Ling Chen; Wenya Liu; Danping Cai; Shuxiang Deng; Hanyu Chu; Ying Liu; Xiangling Feng; Jihua Chen; Mengshi Chen; et al. (Journal of Hazardous Materials, 2023)

Effects of carbonate minerals and exogenous acids on carbon flux from the chemical weathering of granite and basalt - Chaojun Li; Pete Smith; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Qin Li; Jinfeng Wang; Luhua Wu; Fei Chen; Yuanhong Deng; Zeyin Hu; Yujie Yang; et al. (Global and Planetary Change, 2023)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

Therapeutic effect of the sulforaphane derivative JY4 on ulcerative colitis through the NF-κB-p65 pathway - Xiu-Juan Zhao; Yi-Ran Zhang; Wen-Fei Bai; Tong-Yan Sun; Yu-Fen Yang; Tong-Xin Wang; Cui-Gai Bai (Inflammopharmacology, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

BmK DKK13, A Scorpion Toxin, Alleviates Pain Behavior in a Rat Model of Trigeminal Neuralgia by Modulating Voltage-Gated Sodium Channels and MAPKs/CREB Pathway - Ran Yang; Yongbo Song; Haipeng Wang; Chunyun Chen; Fei Bai; Chunli Li (Molecular Neurobiology, 2022)

Carbon storage of the forest and its spatial pattern in Tibet, China - Long-yu Jia; Gen-xu Wang; Ji Luo; Fei Ran; Wei Li; Jun Zhou; Dan-li Yang; Wen-bo Shi; Qian Xu; Kun Zhu; Yang Yang (Journal of Mountain Science, 2021)

Heavy metal contamination in surface sediments from lakes and their surrounding topsoils of China - Minghao Wang; Xiaoyang Liu; Bing Yang; Yang Fei; Jingjing Yu; Ran An; Lijie Duan (Environmental Science and Pollution Research, 2021)

Comprehensive Marine Observing Experiment Based on High-Altitude Large Unmanned Aerial Vehicle (South China Sea Experiment 2020 of the “Petrel Project”) - Xuefen Zhang; Liangxu Li; Rongkang Yang; Ran Guo; Xia Sun; Jianping Luo; Hongbin Chen; Daxin Liu; Kebing Tang; Wenwu Peng; Xiaodong Han; Qiyun Guo; et al. (Advances in Atmospheric Sciences, 2021)

Apple MdSAT1 encodes a bHLHm1 transcription factor involved in salinity and drought responses - Yu-Ying Yang; Peng-Fei Zheng; Yi-Ran Ren; Yu-Xin Yao; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Planta, 2021)

New insights into the mechanism of storage protein biosynthesis in wheat caryopsis under different nitrogen levels - Xurun Yu; Leilei Wang; Liping Ran; Xinyu Chen; Jieyue Sheng; Yang Yang; Yunfei Wu; Gang Chen; Fei Xiong (Protoplasma, 2020)

Cloning and functional identification of a strigolactone receptor gene MdD14 in apple - Yu-Ying Yang; Yi-Ran Ren; Peng-Fei Zheng; Ling-Ling Zhao; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Formation of Protein Bodies and the Response to Nitrogen in Different Positions During Wheat Endosperm Development - Yang Yang; Xinyu Chen; Liping Ran; Yunfei Wu; Xurun Yu; Zhaodi Dong; Fei Xiong (Journal of Plant Biology, 2019)

Mild Hypothermia Prevents NO-Induced Cytotoxicity in Human Neuroblastoma Cells Via Induction of COX-2 - Bing-Bing Lei; Fei Ju; Qi-Ran Fu; Xin Yuan; Wen-Xin Song; Guo-Qin Ji; Kai-Yu Lei; Lei Wang; Bin-Feng Cheng; Mian Wang; Hai-Jie Yang (Journal of Molecular Neuroscience, 2019)

Allometric equations of select tree species of the Tibetan Plateau, China - Fei Ran; Rui-ying Chang; Yang Yang; Wan-ze Zhu; Ji Luo; Gen-xu Wang (Journal of Mountain Science, 2017)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)

Soil microbial community composition and its driving factors in alpine grasslands along a mountain elevational gradient - Hai-jun Cui; Gen-xu Wang; Yan Yang; Yang Yang; Rui-ying Chang; Fei Ran (Journal of Mountain Science, 2016)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

Analysis of quality factors for Rayleigh channel waves - Xiao-Hui Yang; Si-Yuan Cao; De-Chun Li; Peng-Fei Yu; Hao-Ran Zhang (Applied Geophysics, 2014)